Keserasian Dua Dunia yang Berbeda: Relasi ASEAN-EU dalam Kerja sama Multilateral - Rr. Nurul Rahmah C.P; Ridwan Stanley Sinaga; Adi Fadhilah Nurul Rahman; Enno Nuri Al Sarah; Hari Agung Satya Wicaksana; Mutiara Megantari Putri; Khansa Hanun Augie (Universitas Diponegoro, 2018)
Cooperation could be done by integrated cooperation between states member and inter regional organization equally, like ASEAN and EU (Eropean Union) cooperation. Popular speculations between this two organizations are mostly partial, biased in gap between EU contribution to ASEAN rather than vice versa. In this paper, we challenge capability of ASEAN as a regional organization with most of the member states are developing and third world country comparing to EU which 26 of members states has highest GDP all around the world. This paper also discuss about ASEAN as an organization that have eperiences in several humanitarian violation cases, comparing with EU as a ‘safe heaven’ in human rights. Through ecleckticism theory, we would see how liberalism and realism played a role in seeing such phenomenon, and how to see between those two theories. This paper argEUs that there are mutuliasm cooperations between EU and ASEAN, start with EU contribution on ASEAN structures, the critics about ASEAN as ‘imitation community’, and also being partner with ASEAN in investments. ASEAN is also seen as a ‘teacher’ for EU in pragmatism and normative power to improve EU capability as inclusive community.Keywords: trade, hegemony, multilateral, EU, ASEAN